The Campo de Calatrava Volcanic Field (central Spain): Fluid geochemistry in a CO2-rich area. (March 2019) - Nisi, B.; Vaselli, O.; Elio, J.; Giannini, L.; Tassi, F.; Guidi, M.; Darrah, T.H.; Maletic, E.L.; Delgado Huertas, A.; Marchionni, S.
Abstract: The Campo de Calatrava Volcanic Field (CCVF) located in central-southern Spain (along with Selva-Emporda in Catalonia, NE Spain) is regarded as one of the most important CO2 emitting zones in Peninsular Spain. Here, we report and evaluate new molecular and isotopic geochemistry of thermal waters and CO2- rich gas discharges from the CCVF. Locally, these CO2 -rich fluid emissions represent the remnants of the past volcanic activity that affected this area from the late Miocene through the Quaternary, with the most recent events occurring in the Holocene. The locations of discharging fluids and previous volcanic centers appear to be aligned along well-defined NW-SE and NNW-SSE lineaments, with subordinate trends in the ENE-WSW direction. The chemical and isotopic composition of the thermal waters suggests a meteoric origin, dominated by three distinct geochemical facies: 1) HCO3 -Mg(Ca) type waters, associated with a relatively shallow aquifer and related to the interaction of meteoric waters with CO2 -rich gases, alkaline volcanic products, and sedimentary formations, 2) SO4 (Cl)-Ca(Mg) type waters, which stems from the two rivers (Guadiana and Jabalón) that drain Triassic evaporitic rocks before entering the study area, and 3) HCO3 -Na type waters, hosted in deep geopressurized CO2 -rich reservoirs within the Ordovician basement rocks. The 87 Sr/ 86 Sr isotopic compositions (ranging between 0.70415 and 0.71623) and δ 34 S-SO4 values (+10.7 to +18.3‰ vs. CDT) of CO2 -rich fluids are consistent with interactions between water and either the Paleozoic basement, Triassic evaporites, Quaternary volcanic rocks, or a combination thereof. Dissolution of a CO2 -rich gas phase into the aquifer produces low pH values (down to 5.4) and enhances water-rock interactions causing relatively high salinity (Total Ionic Salinity: up to ∼185 meq/L). Carbon dioxide is by far the most abundant gas constituent (up to 992 mmol/mol) and is dominated by mantle-derived sources as indicated by the combination of relatively high helium isotopic ratios (up to 2.7 R/Ra), high isotopic ratios of carbon in CO2 (ranging between −6.8 and −3.2‰ V-PDB), and the carbon isotopic signature of TDIC (from −6.8 to +2.2‰ vs. VPDB). In the last two decades, numerous (CO2 -rich) gas blowouts have occurred in the area during well drillings, suggesting the presence of a geopressurized gas reservoir at relatively shallow depth. Highlights: Fluid geochemistry of the Campo Calatrava Volcanic Field (central-southern Spain). The CO2 -rich gases likely are the ultimate remnants of the past volcanic activity. Presence of a CO2 -pressurized reservoir at a relatively shallow depth. Gas geochemistry suggests the evidence of a mantle-derived volcanism. A conceptual model based on geochemical and isotopic data is presented.